Divorce Mediation in Islamic Family Law: Assessing the Role of Religious Mediation in Conflict Resolution - Sulistiawati, Lina (Journal of Islamic Family Law, 2025)
This study examines the role of religious mediation in divorce cases within Islamic family law, analyzing how it contributes to conflict resolution and whether it aligns with contemporary standards of justice and fairness. A qualitative research approach is employed to collect data from multiple Islamic jurisdictions, focusing on how religious mediation is implemented in practice. Interviews were conducted with mediators, legal professionals, and participants from Saudi Arabia, Malaysia, Indonesia, and Egypt, aiming to capture diverse perspectives on religious mediation's effectiveness in resolving marital disputes. The results of the analysis indicate that religious mediation serves as an essential mechanism for conflict resolution, reflecting a balance between traditional Islamic values and contemporary needs for fair dispute resolution. The findings could serve as a reference for legal scholars, policymakers, and religious authorities who aim to improve the effectiveness of mediation within an Islamic framework.